Nepali-Nature Inspired Making as Climate Solutions - Panneels, Inge (Making Futures Journal, 2021)
Responding to the session one brief Re-crafting the Local-Global Maker Relationship, Inge considers material-based making practices found in the traditional handicraft and design innovation communities in Nepal which fit the mould of a doughnut economics. The current economic model, she argues, is not fit for purpose for the 21st century. Rooted in feminist, gender, race and environmental theory, Doughnut Economics proposes seven new ways to think about economics that puts people and the planet at the heart of a radical new way of thinking about the economy. A circular, economic principle which proposes a closed loop design can be identified in these Nepali craft practices using case studies from the Road to COP26 Innovation Programme, supported by the British Council in Nepal, which took place in Spring 2021. This discovery is situated in a post-colonial context, picking up on the ‘radical indigenism’ of traditional craft practices and expanding on the role of ‘thinking through craft’, whilst considering how ‘making is connecting’ through the Quintuple Bottom Line (profit, people, planet purpose and place), which is used here as a lens to interrogate the Doughnut model. Finally, we will consider how these case studies fit with the model of care. This paper thus provides a timely context of these practices in the lead up to COP26, the global climate summit which will take place in Glasgow in November 202, where countries will be expected to report back on climate action since the Paris Agreement from 2015 and commit to new targets. <div class="U26fgb mUbCce fKz7Od LRAOtb Znu9nd M9Bg4d" role="presentation" aria-describedby="h.k1dj5b8ktt42_l" aria-label="Copy heading link" aria-disabled="false" data-tooltip="Copy heading link" aria-hidden="true" data-tooltip-position="top" data-tooltip-vertical-offset="12" data-tooltip-horizontal-offset="0"> Biography: Dr Inge Panneels, artist and Research Fellow at Edinburgh Napier University (Creative Informatics) is looking at how data and technology is deployed or withheld in the drive to help the creative industries embrace the quintuple bottom line (people, planet, profit, purpose and place). Inge is interested in the role that creativity can play when attempting to implement a culture shift towards a circular economy which operates within social and ecological boundaries. She is a current Trustee of Edinburgh Tool Library and was a senior lecturer on the Artist, Designer, Maker course at the University of Sunderland. She is also a crafts advocate for Creative Arts Business Network (CABN) and a specialist advisor for Creative Scotland and the Scottish Arts Council.